Individualized Cerebral Artery Protection Strategies for the Surgical Treatment of Parasellar Meningiomas on the Basis of Preoperative Imaging - Yang Li (Frontiers Media S.A., 2021)
ObjectiveParasellar meningiomas (PMs) represent a cohort of skull base tumors that are localized in the parasellar region. PMs tend to compress, encase, or even invade the cerebral arteries and their perforating branches. The surgical resection of PMs without damaging neurovascular structures is challenging. This study aimed to analyze functional outcomes in a series of patients who underwent surgery with individualized cerebral artery protection strategies based on preoperative imaging.MethodsA retrospective review was performed on a single surgeon’s experience of the microsurgical removal of PMs in 163 patients between January 2012 and March 2020. Individualized approaches with a bidirectional dissection strategy were used. Cerebral artery invasion classification, neurological outcomes, MRC Scale for muscle strength, and Karnofsky performance scale were used to assess tumor vascular invasion, functional outcome, and patient quality-of-life outcomes, respectively.ResultsTotal resection (Simpson grade I or II) was achieved in 114 patients (69.9%) in our study. A total of 44.7% of patients had improved vision at consecutive follow-ups, 51.1% were stable, and 3.8% deteriorated. Improvements in cranial nerves III, IV, and VI were observed in 41.1%, 36.2%, and 44.8% of patients, respectively. The mean follow-up time was (38.8 ± 27.9) months, and the KPS at the last follow-up was 89.6 ± 8.5. Recurrence was observed in eight patients (13.8%) with cavernous sinus meningiomas, and the recurrence rates in anterior clinoid meningiomas and medial sphenoid wing meningiomas were 3.8% and 2.8%, respectively.ConclusionsPreoperative imaging is important in the selection of surgical approaches. Maximum tumor resection and cerebral artery protection can be achieved concurrently by utilizing the bidirectional dissection technique. Individualized cerebral artery protection strategies provide great utility in improving a patient’s quality of life.